Modified Sprayer Design For Rice Plant Pest Control (Oryza sativa L.) - Dyah Ayu Sri Hartanti; Muhamad Wahyu Dwi Iqbal Bachtiar Bachtiar; Siti Aminatuz Zuhria (AGARICUS: Advances Agriculture Science & Farming, 2026)
The purpose of this study was to design and test the performance of a modified sprayer in controlling rice plant pests. Limitations of the manual sprayer include low capacity, uneven spray distribution, and high labor and time requirements, all of which lead to ineffective pest control. A research and development method was used, which included design, construction, and field testing. The test was conducted for four weeks on rice fields with the same plant spacing. The level of leaf damage due to pest attacks and spraying efficiency were two parameters observed. The results showed that the modified sprayer performed better than the manual sprayer, as indicated by a greater reduction in leaf damage levels during the observation period. In addition, the modified sprayer was able to improve work efficiency by expanding the spray range, speeding up spraying time, and reducing operator workload. In contrast, the manual sprayer showed a slower reduction in damage. These results indicate that the modified sprayer is more effective in supporting pest control and has the potential to be an appropriate technology to improve efficiency, productivity, and sustainability in rice cultivation.